Cancer Therapy: Targeted Dual pH‐Sensitive Lipid ECO/siRNA Self‐Assembly Nanoparticles Facilitate In Vivo Cytosolic sieIF4E Delivery and Overcome Paclitaxel Resistance in Breast Cancer Therapy (Adv. Healthcare Mater. 22/2016). Issue 22 (November 2016) - Gujrati, Maneesh; Vaidya, Amita M.; Mack, Margaret; Snyder, Dayton; Malamas, Anthony; Lu, Zheng‐Rong
Abstract : Zheng‐Rong Lu, Maneesh Gujrati, and co‐workers design and develop simple and smart lipid ECO/siRNA self‐assembly nanoparticles, which can efficiently silence the oncogene, eukaryotic translation initiation factor 4E (eIF4E), and consequently resensitize triple‐negative breast cancer (TNBC) to paclitaxel on page 2882. This approach holds great promise for alleviating drug resistance in cancer therapy. Besides TNBC, the targeted multifunctional ECO/siRNA nanoparticles represent a versatile platform technology for the delivery of therapeutic siRNAs for the treatment of various other human diseases.